Complex neurological symptoms in bilateral thalamic stroke due to Percheron artery occlusion - Caruso P; Manganotti P; Moretti R (Vascular Health and Risk Management, 2016)
Paola Caruso, Paolo Manganotti, Rita Moretti Department of Clinical Neurology, University of Trieste, Trieste, Italy Abstract: The artery of Percheron is a rare anatomical variant where a single thalamic perforating artery arises from the proximal posterior cerebral artery (P1 segment) between the basilar artery and the posterior communicating artery and supplies the rostral mesencephalon and both paramedian territories of the thalami. Almost one-third of human brains present this variant. Occlusion of the artery of Percheron mostly results in a bilateral medial thalamic infarction, which usually manifests with altered consciousness (including coma), vertical gaze paresis, and cognitive disturbance. The presentation is similar to the “top of the basilar syndrome”, and early recognition should be prompted. We describe the case of a young female with this vessel variant who experienced a bilateral thalamic stroke. Magnetic resonance angiography demonstrated bilateral thalamic infarcts and a truncated artery of Percheron. Occlusion of the vessel was presumably due to embolism from a patent foramen ovale. Thrombolysis was performed, with incomplete symptom remission, cognitive impairment, and persistence of speech disorders. Early recognition and treatment of posterior circulation strokes is mandatory, and further investigation for underlying stroke etiologies is needed. Keywords: thalamus vascularization, cognitive impairment, paramedian thalamus territory, speech disorder, vertical gaze palsy